PERBANDINGAN DINAMIKA KELEMBAGAAN EKONOMI ISLAM PADA NEGARA BAHRAIN DAN CHINA TERHADAP INKLUSI KEUANGAN SYARIAH - Anisa Ramadhani; Naufal Luthfi Alifa (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2026)
Islamic finance and banking conditions have experienced growth and are one of the most widely practiced aspects of Muslims seen in Muslim-majority countries such as Bahrain, and have spread to many non-Muslim countries like China that has a small Muslim population, but offers great potential and opportunities to study Islamic financial marketing. The research was conducted by focusing on three main aspects, namely: describing the dynamics of Islamic economic institutions in Bahrain and China, explaining the challenges and strategies for strengthening Islamic economic institutions in facing global challenges in Bahrain and China, and analyzing reflective comparisons of Islamic economic institutions in Bahrain and China. This research uses a qualitative approach by reviewing various national and international journals in the 2016-2025 period. The results of the study show that: (1) Bahrain's success and China's progress show that strengthening Islamic economic institutions through regulations, institutional capacity, and technology can be strategic for expanding Islamic financial inclusion in a sustainable manner; (2) Bahrain's successes and challenges, as well as China's obstacles, demonstrate that the effectiveness of Islamic financial inclusion depends on clear regulations, human resource readiness, digital innovation, and adaptive institutional capacity; (3) Reflecting on Bahrain and China, it is shown that regulatory consistency, institutional capacity, prepared human resources, digital integration, and state involvement are crucial for Islamic financial inclusion, so that Indonesia can strengthen governance, standard harmonization, and regional strategic position.